LARUNG SESAJI PERMANDIAN ALAM LIMBUA MASYARAKAT BULUKUMBA - Nensilianti; Ridwan; Dilla Paramita (Jurnal Bastra (Bahasa dan Sastra), 2024)
Larung Sesaji in Bulukumba is a ritual of expressing gratitude which is carried out at various important moments, such as when someone has certain intentions or after marriage. This tradition attracted the attention of Edward Burnett Tylor, a British anthropologist, who analyzed it as a form of animism, the belief that inanimate objects have spirits. This research uses descriptive qualitative methods with the theoretical anthropological approach of Edward Bunnett Tylor and note-taking and recording techniques to understand the tradition of larung offerings in depth. It is hoped that the research results can explain the meaning and function of this tradition in the lives of the Bulukumba people.